2021
DOI: 10.1007/s12282-021-01221-4
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of SERPINA3 promotes tumor invasion and migration, epithelial-mesenchymal-transition in triple-negative breast cancer cells

Abstract: Background Recent studies have indicated that serpin peptidase inhibitor, clade A, member 3 (SERPINA3) is a potential marker associated with tumor progression, which connoted that SERPINA3 is related to malignant phenotypes in cancer. However, the biological function of SERPINA3 in breast cancer (BC) remains unclear. Methods Bioinformatics data were downloaded from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) databases. Immunohistochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Meanwhile, MCC method of the CytoHubba plug-in was used to calculate the top 5 proteins as hubproteins. In the BF-TK/GCV / BF-TK group, the top 5 hubproteins were AMBP, HRG, APCS, HPX and GIG25 (Figure 4D), some proteins (HRG, HPX and GIG25) are positively associated with tumor metastasis (Mondaca et al, 2021; Niu et al, 2021; Zhang et al, 2021a). Besides, PPI network showed that CEBPB, NF-κB1, MTOR, HIF-1A, VCAM1 and CXCL12 were interacted directly or indirectly (Figure 4E).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, MCC method of the CytoHubba plug-in was used to calculate the top 5 proteins as hubproteins. In the BF-TK/GCV / BF-TK group, the top 5 hubproteins were AMBP, HRG, APCS, HPX and GIG25 (Figure 4D), some proteins (HRG, HPX and GIG25) are positively associated with tumor metastasis (Mondaca et al, 2021; Niu et al, 2021; Zhang et al, 2021a). Besides, PPI network showed that CEBPB, NF-κB1, MTOR, HIF-1A, VCAM1 and CXCL12 were interacted directly or indirectly (Figure 4E).…”
Section: Resultsmentioning
confidence: 99%
“…Hemopexin (HPX) promotes invasion and metastasis of the pancreatic cancer and colorectal carcinoma cells(Niu et al, 2021). GIG25 is a serpin family a member 3 (or SERPINA3) and overexpression of SERPINA3 promotes tumor invasion and migration, epithelial-mesenchymal-transition in triple-negative breast cancer cells(Zhang et al, 2021b). PELO was upregulated by BF-TK/GCV treatment and enriched in mRNA surveillance pathway, However, it was listed out of top 30 pathways (data not showed in Figure 1C).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although its exact biological function is not known, it has been described in association with diverse pathologies, such as acute kidney injury, cardiovascular disease, and (lung) cancer [ 37 , 38 , 39 , 40 ]. It was described to promote metastasis and the epithelial–mesenchymal transition in breast cancer [ 41 ] and was found to be upregulated in lung cancer in comparison to control patients [ 42 ]. In our study, the highest SERPINA3 abundance was found in COPD patients ( Supplementary Figure S3 ), again demonstrating the need for the direct comparison of clinically relevant patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…In prostate cancer, SERPINA3 promotes aerobic glycolysis and autophagy while inhibiting apoptosis of cancer cells ( Xing et al, 2021 ). In glioblastoma and breast cancer, high expression of SERPINA3 is closely related to cancer cell proliferation, invasion, migration, and epithelial-mesenchymal transition, and thus leads to poor prognosis and tumor recurrence ( Nimbalkar et al, 2021 ; Zhang et al, 2021 ). Similar phenomena can also be observed in endometrial cancer, liver cancer, colon cancer and so on ( Cao et al, 2018 ; Ko et al, 2019 ; Zhou et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%